GANDHI IS OF THE FUTURE, NOT OF THE PAST: RELEVANCE OF GANDHI’S ECONOMIC IDEAS IN MODERN INDIA - Mishra , Poonam; Jangid, Shakuntala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mahatma Gandhi was a multifaceted thinker, spiritual saint, statesman and spiritual seer. His aim was to serve the nation and humanity and he undertook various political, social, educational, religious and economic activities. His economic thought was based on moral and ethical principles, influenced by Tolstoy and Ruskin. Gandhi believed that economics which hurts the moral welfare of an individual or a nation is immoral and sinful. He was a practical idealist and opposed modern capitalism, which according to him exploits human labour. Gandhian economic ideas were based on the principle of simple living and high thinking and he believed that the progress of India depended on the development of villages. He stressed the development of rural industries like handloom, handicrafts, khadi and silk production, which were based on family labour and required less capital. He also advocated the development of cottage industries to reduce the burden on agriculture and support the village. Gandhian economic thought was also opposed to machinery, which he considered a ’great sin’. He welcomed tools and machines that saved personal labour and eased the burden of millions of cottage dwellers.